A Rare Bilateral Asymmetric Variation of the Anterior Belly of Digastric Muscle. - Raju S,; Kanchana L,; Venu MN,; Raghu Jetti,; Srinivasa RS, (Department of Surgery, UKM Medical Centre, 2014)
Accessory bellies of digastric muscle may alter the movements of mandible and hyoid bone. Even they cause difficulty in the clinical diagnosis of pathological masses in the submental area and also interfere with successful surgeries in the anterior neck region. The anomalies of the anterior belly of digastric muscle (ABD) are uncommon. However, reporting of possible attachments and arrangement of muscle fibres is of tremendous clinical importance. In the present case, we report bilateral asymmetric ABD in adult male cadaver. Both accessory muscles originated from digastric fossae. Right belly inserted to the median raphe of mylohyoid muscle. Left belly had two segments: upper anterior segment inserted to the median raphe whereas the lower posterior segment inserted to the median raphe and ipsilateral intermediate tendon. Accessory bellies of anterior belly reported here is unique in their arrangement and documentation of such observation may add further information to existing literature.